Analisis Komponen dan Model dalam Pengembangan Sistem Informasi Akuntansi - Grace Putri Johana; Gloria Sthefany; Maria Grace Pane; Esa Setiana (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2025)
This study discusses the urgency of developing an Accounting Information System (AIS) in the face of modern business dynamics that demand speed, accuracy, and transparency of financial information. AIS plays an important role in providing relevant data for managerial decision-making, while maintaining the trust of external parties. However, technological developments, regulatory changes, and business complexity mean that outdated systems risk losing their relevance. This study uses a qualitative descriptive approach based on literature review with content analysis techniques on books, journals, and academic publications. The focus of the study includes the urgency of MIS development, key components to consider (needs analysis, database design, integration, security, automation, reporting, and evaluation), development models (Waterfall, Iterative, and Spiral), and evaluation stages to ensure the system meets organizational needs. The results of the study show that MIS development contributes significantly to improving the efficiency, effectiveness, and competitiveness of companies. Continuous evaluation is a key factor in maintaining the relevance of the system to technological developments and business needs. Thus, planned and structured MIS development is not only a technical solution but also a business strategy that supports organizational sustainability.